THE USE OF EXTENSIVE READING ACTIVITIES TO IMPROVE STUDENTS` CRITICAL THINKING SKILL - Umam, Farid Khoirul; ., Hartono; Hidayati, Nani; Ningsih, Nur Eka (Jurnal Ilmiah Penelitian Mahasiswa, 2024)
The Use of Extensive Reading Activities to Improve Students` Critical Thinking Skill. The aim of this study was to find out whether extensive reading activities are effective to improve the 11th graders’ critical thinking skills at MA Thoriqotul Ulum Pati in academic year 2023/2024. The type of this study was a quasi-experimental design and the method was quantitative. The population of this study was the 11th graders of MA Thoriqotul Ulum Pati and the sample consisted of 19 students of XI MIPA as the experimental class and 18 students of XI IPS as the control class. Face and content validity was done to know the validity and reliability for the instrument. Pre-test and post-test were given to experimental and control class. The result of the pre-test for experimental was 72.11 and the control class was 60.28. While the result of post-test of the experimental class was 88.16 and the control class was 67.22. The test results using the Mann-Whithney test obtained a ρ value of 0.000 < α 0.05 so that Ho is rejected, meaning that there is a significant difference in critical thinking skills between students who did an extensive reading activity and those who did not do an extensive reading activity. Keywords: Extensive Reading activities, Reading comprehension, Critical Thinking skill